Impaired central sensitivity to thyroid hormone is associated with hypertriglyceridemia in euthyroid population - Gong, Yu; Wang, Guojuan; Zhang, Qianqian; Jiang, Xu; Zhu, Zhangxiang; Li, Ying (Frontiers in Endocrinology, 2025)
BackgroundWe aimed to investigate the correlation between central thyroid hormone sensitivity and Hypertriglyceridemia (HTG) in euthyroid population.MethodsA total of 833 individuals who underwent physical examinations were randomly selected. Biochemical parameters including thyroid hormones (THs), liver and kidney functions, blood glucose, and blood lipids were measured. Central TH sensitivity was evaluated using the thyroid feedback quantile-based index (TFQI), thyroid-stimulating hormone index (TSHI) and thyrotropin thyroxine resistance index (TT4RI). ​​ We analyzed the relationship between central TH sensitivity and triglyceride (TG) level using smooth curve fitting and threshold effect analysis and trend tests in multiple regression equations.​ResultsTSHI (β=0.158, P=0.0443) was positively correlated with TG, while TT4RI (β=0.018, P=0.0112, inflection point: 25.809) and TFQI (β=0.798, P=0.0066, inflection point: -0.194) were both positively correlated with TG before the inflection points. Subgroup analyses revealed these relationships were particularly pronounced in females (TT4RI β=0.026, P=0.0205, inflection point: 22.487; TFQI β=0.780, P=0.0133, inflection point: -0.142), males (TFQI β=1.954, P=0.0100, inflection point: -0.395), individuals with age <65 years (TT4RI β=0.019, P=0.0119, inflection point: 25.809; TFQI β=0.878, P=0.0060, inflection point: -0.206), and individuals with BMI<28kg/m² (TT4RI β=0.026, P=0.0090, inflection point: 21.515; TFQI β=0.735, P=0.0132, inflection point: -0.173), all showing positive correlations before the point correlations. Tests for trend in multiple regression equations showed that with the increased quartiles of TT4RI (OR=1.321, P=0.00118) and TSHI (OR=1.253, P=0.00784), the risk of HTG increased correspondingly. For per SD increase in TT4RI, the odds of HTG increased by 36.5% (OR=1.365, P=0.00703). For per SD increase in TSHI, the odds of HTG increased by 19.1% (OR=1.191, P=0.06648).ConclusionImpaired central thyroid hormone sensitivity is associated with increased triglyceride in euthyroid population, this association is more pronounced in individuals with aged<65 years and BMI<28kg/m2. Impaired central thyroid hormone sensitivity may be an independent risk factor for hypertriglyceridemia.